Fetal heart rate mirrors maternal temperature during posterior fossa craniotomy: a case report. (August 2021) - Sastry, A.C.; Gandhi, M.; Clark, S.L.; Whitehead, W.E.; Mann, D.G.; Sutton, C.D.
Highlights: Maternal hypothermia may affect baseline fetal heart rate and variability. Differential diagnosis for fetal heart rate changes includes maternal temperature. Maternal temperature should be monitored and regulated during non-obstetric surgery. Abstract: While it is well known that maternal temperature affects fetal heart rate, the exact relationship is not well described. The circumstances accompanying most cases of maternal hypothermia and rewarming (e.g. a drowning event) have precluded a precise quantitative description of this relationship. We describe hypothermia and controlled rewarming during resection of a maternal brain stem tumor in the early third trimester. Continuous electronic fetal heart rate and core temperature monitoring demonstrated a near linear relationship during the development of hypothermia and rewarming. Recognition of the close relationship between maternal temperature and fetal heart rate can help safeguard maternal and fetal health, and prevent unnecessary delivery during non-obstetric surgery in pregnancy.